Châtelperronian cultural diversity at its western limits: Shell beads and pigments from La Roche-à-Pierrot, Saint-Césaire - François Bachellerie; Brad Gravina; Solange Rigaud; Laure Dayet; Marc Thomas; Loïc Lebreton; Eugène Morin; Camille Lesage; Christophe Falguères; Edouard Bard; Jean-Jacques Bahain; Mickaël Baillet; et al. (Proceedings of the National Academy of Sciences, 2025)
The timing and mechanisms underlying the gradual replacement of Neanderthal populations by Homo sapiens groups have elicited heated debate for decades. The Châtelperronian of France and northern Spain has figured prominently in these discussions. While the Neanderthal authorship of this techno-complex is far less certain than previously thought, the Châtelperronian is now generally accepted as being among the first genuine Upper Paleolithic industries in Eurasia rather than a “transitional” stone tool technology. Here, we report the first association of shell beads with Châtelperronian artifacts from new excavations at the site of La-Roche-à-Pierrot, Saint-Césaire (France), supported by a multiproxy spatial analysis that incorporates site formation processes. Similar types of personal ornaments are unknown from Middle Paleolithic contexts. Comparable examples have, however, been recovered from contexts penecontemporaneous with the Châtelperronian in south-eastern Europe and around the Mediterranean. This hitherto undocumented combination of an early Upper Paleolithic industry and shell beads provides insights into cultural variability in western Europe and raises the question as to whether the makers of the Châtelperronian were influenced by or formed part of the earliest dispersals of H. sapiens into the region.